2019
DOI: 10.1002/app.48752
|View full text |Cite
|
Sign up to set email alerts
|

Polyurethane foaming with CO2 adducts from C8 alkyl grafted polyethyleneimines: Optimization of the grafting rate and application of the blowing agents

Abstract: We previously explored a series of CO2 adducts from alkylated polyethylenimines with C4 to C16 alkyl side chains, serving as climate‐friendly blowing agents for polyurethanes (PUs). Among them, the polyethylenimine with C8 alkyl (2‐ethylhexyl) side chains demonstrated the highest foaming efficiency. In this study, we further changed the grafting rate of the C8 alkyl, from 7 to 16%, and investigated the effects of the resulting blowing agents on the foaming process. For both foaming systems containing a castor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Figure 9: Ionic carbamate salts for the preparation of (a) epoxy (Adapted with permission from [56]. Copyright (2015), American Chemical Society) and (b) PU foams (Adapted with permission from [146] Copyright (2019) Wiley Periodicals, Inc).…”
Section: Ionic Carbamatesmentioning
confidence: 99%
“…Figure 9: Ionic carbamate salts for the preparation of (a) epoxy (Adapted with permission from [56]. Copyright (2015), American Chemical Society) and (b) PU foams (Adapted with permission from [146] Copyright (2019) Wiley Periodicals, Inc).…”
Section: Ionic Carbamatesmentioning
confidence: 99%
“…127 However, Da et al presented the synthesis of a PU foam using both primary and secondary carbonated amines. 128 They notably discussed the effect of the steric hindrance on the secondary amine and reported that primary amine was more difficult to decarbonate at 100°C. The carbon dioxide is an interesting gas to produce since it is non-toxic and non-flammable.…”
Section: Scheme 15 : Amine Carbonation Mechanism 111mentioning
confidence: 99%
“…Previous undertakings have demonstrated that highly dispersible modified PEI-CO 2 blowing agents can facilitate the formation of PUFs with small cells. 26,28,34…”
Section: Pu Foaming With the Co 2 Adductsmentioning
confidence: 99%
“…We have successfully prepared hydrophobically modified polyethylenimines (PEIs), which can absorb CO 2 and then release CO 2 as a climate friendly blowing agent during the PU foaming process. [26][27][28] In this study, we adopted the Atherton-Todd reaction 29,30 to graft DOPO onto PEI backbones, and used the grafted PEIs to absorb CO 2 , obtaining a new kind of CO 2 adducts of PEIs that might serve as both blowing agents and flame retardants for PUs. The effects of the grafting rate on foaming process, mechanical properties and flame retardancy were investigated.…”
Section: Introductionmentioning
confidence: 99%